Mathematics and scientific representation - Pincock, Christopher (New York ; Oxford : Oxford University Press, 2012)
Mathematics plays a central role in much of contemporary science, but philosophers have struggled to understand what this role is or how significant it might be for mathematics and science. Pincock tackles this perennial question by asking how mathematics contributes to the success of our best scientific representations.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Includes bibliographical references and index.
Keywords: Science -- Mathematics; Science -- Methodology